Plant Pathology : Techniques and protocols - Burns, Robert; Ed (Humana Press, 2009)
Plant diseases can impact enormously on our lives. In this book, expert researchers provide methods which are vital to the diagnosis of plant diseases across the globe. This indispensable guide is written by experts from internationally renowned institutions.